Paratesticular Fibrous Pseudotumor in Children: A Case Report and Review of Literature. Issue 5 (July 2019) - Miscia, Maria E.; Cecinati, Valerio; Fusillo, Mario; Persico, Antonello; Lauriti, Giuseppe; Lisi, Gabriele; Lelli Chiesa, Pierluigi
Abstract : Background: Paratesticular fibrous pseudotumor (PFP) is a rare benign tumor that can mimic malignant tumors; thus, radical orchiectomy was the standard treatment in the past. Observation: A 15-year-old boy came to our attention for a hard right inguinal swelling. An ultrasound showed a highly vascularized mass. The boy underwent a gonadal-sparing excision of the mass that was diagnosed to be a PFP. The patient recovered well, without recurrences at the follow-up. Conclusions: PFP is mostly asymptomatic, and its diagnosis is incidental. Only further 4 pediatric cases were reported in the literature. Our case confirms that gonadal-sparing surgery is an optimal treatment.